2022
DOI: 10.1007/s10067-022-06482-8
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of structural MRI studies of the brain in systemic lupus erythematosus (SLE)

Abstract: A comprehensive search of published literature in brain volumetry was conducted in three autoimmune diseases — systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and ulcerative colitis (UC) — with the intention of performing a meta-analysis of published data. Due to the lack of data in RA and UC, the reported meta-analysis was limited to SLE. The MEDLINE database was searched for studies from 1988 to March 2022. A total of 175 papers met the initial inclusion criteria, and 16 were included in a ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…1 Zahra M Najeeb, 2 Andreas Jönsen, 2,3 Kristoffer Zervides, 3 Petra C Nilsson, 2 Anders Bengtsson, 1 Tim Salomonsson, 4,5 Gregory Kuchcinski, 1,6,7 Pia C Sundgren, Objective Systemic lupus erythematosus (SLE) often presents with neuropsychiatric (NP) symptoms, including cognitive impairment and depression. Past magnetic resonance imaging (MRI) research on hippocampal (HC) volumes, important for NP symptoms, in SLE patients yielded conflicting results and did not investigate other medial temporal lobe (MTL) regions.…”
Section: P40 Medial Temporal Lobe Subregion Volumes In Systemic Lupus...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Zahra M Najeeb, 2 Andreas Jönsen, 2,3 Kristoffer Zervides, 3 Petra C Nilsson, 2 Anders Bengtsson, 1 Tim Salomonsson, 4,5 Gregory Kuchcinski, 1,6,7 Pia C Sundgren, Objective Systemic lupus erythematosus (SLE) often presents with neuropsychiatric (NP) symptoms, including cognitive impairment and depression. Past magnetic resonance imaging (MRI) research on hippocampal (HC) volumes, important for NP symptoms, in SLE patients yielded conflicting results and did not investigate other medial temporal lobe (MTL) regions.…”
Section: P40 Medial Temporal Lobe Subregion Volumes In Systemic Lupus...mentioning
confidence: 99%
“…Past magnetic resonance imaging (MRI) research on hippocampal (HC) volumes, important for NP symptoms, in SLE patients yielded conflicting results and did not investigate other medial temporal lobe (MTL) regions. 1 Our study aims to compare MTL subregional volumes in SLE patients to healthy individuals (HI) and explore the relationship between MTL subregional volume, cognition, and depression in SLE patients. Methods 70 SLE patients (mean age 36 years (range 18-51), mean disease duration 11.1 ± 8.0 years) and 25 HI (mean age 37.2 years (range 23-52)) underwent clinical evaluation, cognitive testing using CNS Vital Signs (CNS-VS), and 3 tesla MRI.…”
Section: P40 Medial Temporal Lobe Subregion Volumes In Systemic Lupus...mentioning
confidence: 99%
“…Involvement of the spinal cord, basal meninges or cranial nerves tends to favour NS over primary CNS vasculitis [62]. Structural brain abnormalities in patients with systemic lupus erythematosus are often detected in patients with similar original presentation [63]. Granulomatosis with polyangiitis and neuro-Behcet's disease can also present with white matter lesions and a pachymeningitis [64].…”
Section: Autoimmune Differential Diagnosesmentioning
confidence: 99%
“…This central representation of the immune system is expected to be manifested across multiple brain modules that can encompass the complexity of the immune response. Indeed, it was shown that peripheral inflammation results in increased activity across the entire brain [14][15][16]. Here, we will focus on the IC, or insula, considered the "primary interoceptive cortex" [4] and highlight some of this region's unique properties, positioning the IC as a key component in immunoception.…”
Section: Immunoceptionmentioning
confidence: 99%
“…It is now well established that the brain responds to changes in peripheral inflammation [14][15][16]. The most intuitive example is sickness behavior, in which physiological and behavioral processes, including sleep, appetite, mood, and cognition, are altered during inflammation or infection [32][33][34][35][36].…”
Section: Evidence For the Involvement Of The Insular Cortex In Immune...mentioning
confidence: 99%